2013
DOI: 10.1111/1751-2980.12104
|View full text |Cite
|
Sign up to set email alerts
|

Peptic ulcer bleeding in China: A multicenter endoscopic survey of 1006 patients

Abstract: The study suggests that the proportions of high-risk PUB in China is 43.4%, while rebleeding and surgery rate after endoscopic treatment as well as the mortality rate of high-risk PUB in China are 15.6%, 1.8% and 0.5%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
(27 reference statements)
1
10
3
Order By: Relevance
“…There were 17.74% patients with Forrest classification Ia and Ib and 1.6% with Forrest IIa, which was different from 12% and 8% in previous report [22]; but the total percentage of Forrest Ia, Ib and IIa was comparable (19.35% vs. 20%). The worse coagulation function and lower platelet count in cirrhotic patients with peptic ulcer bleeding may partly explain it.…”
Section: Discussioncontrasting
confidence: 79%
“…There were 17.74% patients with Forrest classification Ia and Ib and 1.6% with Forrest IIa, which was different from 12% and 8% in previous report [22]; but the total percentage of Forrest Ia, Ib and IIa was comparable (19.35% vs. 20%). The worse coagulation function and lower platelet count in cirrhotic patients with peptic ulcer bleeding may partly explain it.…”
Section: Discussioncontrasting
confidence: 79%
“…The involved endoscopic centers had been collaborated for clinical research for a long time, and majority of the endoscopic centers in this study were also involved in other 2 Chinese national studies [7,8], therefore the agreement among these assessors was generally good.…”
Section: Methodsmentioning
confidence: 98%
“…[8] In this study, Forrest classification was chosen to be the gold standard to define high-risk NVUGIB (Forrest I-IIb) and low-risk NVUGIB (Forrest IIb and III). [13] It was found that high-risk NVUGIB was diagnosed in 184 (32.34%) cases, and low-risk NVUGIB was diagnosed in 385 (67.66%) cases, which was a little bit different from what Li [12] reports in 2014. Li found that 437 (43.4%) were categorized with low-risk peptic ulcer bleeding (Forrest I-IIb) in a multicenter endoscopic survey of 1006 patients.…”
Section: Discussionmentioning
confidence: 74%
“…Given in the Asia-Pacific Working Group consensus in 2011, an adherent clot on a peptic ulcer should be treated with endoscopy combined with a PPI if the clot cannot be removed, [4] Forrest I to IIb was defined as high-risk NVUGIB, and Forrest IIc and III as low-risk NVUGIB in our study. [12][13][14] Statistical evaluations were carried out using the SPSS (Statistical Package for Social Sciences) 13.0 software package. Numerical data were expressed as means ± standard deviation (SD) and categorical variables as means (ratio).…”
Section: Methodsmentioning
confidence: 99%